Temporal dynamics of antimicrobial resistance gene abundances in chicken manure and anaerobic digestate - Atanasova, Aleksandra; Amon, Thomas; Roesler, Uwe; Friese, Anika; Merle, Roswitha; Kabelitz, Tina (Frontiers in Antibiotics, 2025)
IntroductionAntimicrobial resistance (AMR) can spread in microorganisms through the transfer of antimicrobial resistance genes (ARGs). Livestock husbandry is one of the pathways for AMR emergence and transmission. Chicken manure contains valuable nutrients for agricultural field fertilization and can be used as input material for biogas production by anaerobic digestion (AD). However, usually, chicken manure also contains quite high levels of ARGs. In this study, we investigated the presence and temporal dynamics of ARGs against different antibiotic classes in chicken manure and anaerobic digestate as a source of AMR spread.MethodsTo get an overview of the ARG profiles, we quantified the abundances of 374 ARGs by high-throughput (HT)-PCR. We studied eight selected ARGs (tetA, tetX, sul1, sul2, lnuF, emrD, aadA, and tnpA) using qPCR in chicken manure from different flocks and animal ages and in digestate from different AD time points.ResultsChicken manure showed higher amounts of ARGs compared to digestate, which was characterized by a higher ARG diversity. We observed that the effect of chicken age differed between the flocks. ARG abundances in digestate from different time points and different treatment conditions did not exhibit major changes.ConclusionThe flocks’ variability had no relevant effect on ARG abundances in chicken manure, likely due to similar growth conditions. However, manure ARG content increased with the age of the chickens. In our experimental batch setup, AD was more effective in reducing AMR microorganisms than reducing ARGs. Further investigations on process optimization or the application of pre-treatment methods could enhance ARG reduction. Notably, pre-mixing chicken manure with material from a biogas plant prior to processing resulted in a lower ARG load compared to untreated chicken manure.